LITERASI NUMERASI PESERTA DIDIK DALAM PENGGUNAAN MEDIA PEMBELAJARAN DENGAN ISPRING 11 - Abdullah, Anisyah; Agustiani, Riza; Zahra, Atika; Putri, Agustiany Dumeva (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
The low level of numeracy literacy in Indonesia is due to the material tested on TIMSS and PISA, which consists of questions in real-life context problems. Students are not accustomed to solving real problems and cannot analyze information in various forms. The lack of engaging learning materials contributes to students' boredom and makes it difficult for them to tackle numeracy and literacy challenges. This study investigates how well students can read and compute after using the iSpring 11 learning resources. Twenty students from class VII at State Junior High School 46 Palembang were the research subjects. The research method used is design research with a development study, which at the prototype stage uses the Tessmer model. The focus of discussion in this research is the results of the field test stage, where data collection techniques include tests and interviews. Data analysis techniques include test data analysis and interview analysis. This research demonstrates that students' numeracy literacy skills are excellent, with an average score of 88 after learning using the iSpring 11 learning media.